Potential medicinal plants from Sungai Rawog Conservation Area: Documentation and a preliminary phytochemical screening on potential medicinal plants - Avelinah Julius; Hilda Tee; Julianah Awang; Andi Maryani Andi Mustapeng; Suzana Sabran (Sabah Forestry Department, 2024)
Previous botanical surveys on vascular plants in Sungai Rawog Conservation Area (SRCA) have recorded 572 taxa, of which 124 are endemic to Borneo. Of these, only 18 taxa have been listed as known medicinal plants compared to the existing checklist used by the Indigenous people of Sabah. The number may not represent the total known medicinal plants in the studied area because some plants may have medicinal value yet to be explored. Thus, the present study aims to document and conduct phytochemical screening on selected potential medicinal plants from SRCA. The phytochemical detection for alkaloids, flavonoids, phenolics, and saponin was performed using Mayer's reagent, the Shinoda test, the Ferric chloride colour test, and the Froth test, respectively. A total of 90 taxa from flowering plants and ferns have been screened for their phytochemical compounds and identified as having potential medicinal value. Of the 90 taxa, 89 were found to be positive for phenolics, 51 for saponin, 44 for alkaloids, and 28 for flavonoids. The findings could provide a basis for selecting high-potential plants from SRCA for future in-depth chemical and pharmacological studies.